Employees’ training to master digital tools in the process of modeling pedagogical design for work programs in the disciplines’ psychological cycle - O. I. Shcherbakova (Цифровая социология)
Objectives of the training program “Pedagogical design tools digital learning content” are: the training program’s development and testing of digital educational technology instructional design for the teaching staff of the university in the blended learning; system formation of knowledge about digital literacy and digital competence; learning the digital learning technologies’ use in the work programs of the psychological disciplines’ unit in the context of a hybrid learning. Before conducting the teaching, the author conducted a survey of the participants, which demonstrated that 77 % of respondents are willing to learn new skills; 74 % view learning as a question of personal responsibility; 80 % sure that they can adapt to new technologies in the teaching of their subject. 72 % of respondents said that they had not used digital tools before. The results also showed that the motivation for the training of teachers was an inner desire to be a professional (35,8 %); the striving for new knowledge (42,9 %). The requirement for mandatory training is important for one third of the members. The basis of training is founded on the Model 6D (6 disciplines) developed by Roy Pollock with colleagues. To help our teachers the author was developed guidelines for the development of digital skills among teachers and recorded online course (use the following tools: “Mentimetr” for training and development of personnel in the organization in the competence management system; “SessionLab” – for training of employees in the company; “Kahoot” to check the students’ knowledge on the employees’ development in the company and for online interaction; “WhenSpeak” – for analysis the performance of a corporate university, alternative methods of training and personnel development; Board “Lino” was used as an example of work on social learning within the team).